Análise Comparativa dos aspectos físico-químicos e microbiológicos de méis de abelhas sem ferrão melipona fasciculata e Melipona Flavolineata produzidos no município de Curuçá, Pará, Amazônia, Brasil - VALE, Lorena Géssica Carvalho do (2024)
The objective of this study was to analyze the microbiological and physicochemical aspects of honeys from Melipona fasciculata (Grey Uruçu) and Melipona flavolineata (Yellow Uruçu) stingless bees produced by the Meliponicultores Association of Curuçá (ASMELC) and als by non-members from the municipality of Curuçá, Pará, in order to perform a comparative analysis between the honeys of these two bee species. The municipality of Curuçá becomes elevant for research on meliponiculture due to the majority of its territory being within the Mãe Grande Marine Extractive Reserve and the existence of an association in the municipality that specifically encompasses honey producers from the Melipona genus, the ASMELC. Were carried three microbiological tests and eleven physicochemical tests required by the legislation of honey from the Agricultural Defense Agency of Pará (ADEPARÁ) and the Ministry of Agriculture, Livestock, and Supply (MAPA), as well as scientific literature, were conducted on seventeen samples to verify if the honey produced by these beekeepers complied with the standards for human consumption. The majority of the physicochemica test results were within the limits set by legislation and scientific recommendations, as were the microbiological test results. Based on the test results, it can be concluded that the honey from both species studied differ significantly from each other.